Anima, Spiritus, Mens in Sepulchral Inscriptions from the Carmina Latina Epigraphica. Philological Approximations - Gacia, Tadeusz (Verbum Vitae, 2022)
The subject of this study is the meaning of the words anima, spiritus and mens in the metrical sepulchral inscriptions in the Carmina Latina Epigraphica collection published at the end of the 19th century by Franz Buecheler. This collection comprises almost 1,900 texts, of which around 1,400 are funerary and, particularly, sepulchral inscriptions. This article consists of three sections. The first contains general comments on Roman sepulchral inscriptions. The second, and most important part uses a conventional philological method to analyze the words in the source texts that denote the immaterial aspect of the human being that continues after death. The analysis of the texts reveals that the word anima occurs about 80 times, spiritus – 20, and mens only three times. These three words stand for what is usually expressed by the word “soul,” that is, the spiritual, immaterial aspect of the human being. Conclusions are presented gradually as the analytical compilation proceeds. Firstly, there is no semantic difference between anima and spiritus; although the word animus which is close to the three words discussed in this paper does not occur in this sense in the inscriptions. Secondly, both pagan and Christian inscriptions emphasize the dichotomy between anima or spiritus and corpus or caro (alternatively membra); some Christian inscriptions, pointing to this dichotomy, express belief in the resurrection. Thirdly, despite the difference in beliefs, Roman worshipers and Christians used very similar patterns of statements about the posthumous fate of the soul, for example, astra tenent animam, astra fovent animam, anima migravit ad astra or spiritus astra tenet, spiritus petit ad astra, mens caeli perget ad astra, which means that the Christian funerary language did not develop its distinct terminology for several centuries. The third section is a very brief summary of the study carried out.